Deradikalisasi Agama di Era Digital Melalui Pendidikan Islam Multikultural - Sukarman Sukarman; Raharjo Raharjo; Fatah Syukur (Journal of Islamic Studies and Humanities, 2019)
The rise of radical intolerant understanding, the spread of the movement of exclusivity and fundamentalism of Islamic teachings poses a serious threat to internal Muslims and the global community. This phenomenon has an impact on the emergence of disputes between groups, internal and external to Muslims, which endangers the survival of the global community. Especially in the digital age where information flow seems to be in the grip. Everyone easily accesses and disseminates information, very easily. Although the digital era has positive impacts, the negative impacts are no less terrible. Through sophisticated electronic devices that collaborate with the development of information technology dissemination of negatively charged content such as hate speech, hoaxes, radical propaganda and streams that threaten public harmony spread easily and can be accessed by anyone and anywhere. The real concern is not only in the general public, but among adults and educated people, but the younger generation is also potentially exposed to these things. To stem the onslaught of intolerant radical radical propaganda, the right solution is to counter this, namely multicultural Islamic education. Multicultural Islamic education is expected to be a surefire solution to the problem. The atmosphere is that the spirit of Islam as a religion that spreads mercy for all nature will be truly realized. Through case study research and qualitative approaches, this paper examines how radicalism, fundamentalism and exclusivity of Islamic teachings spread easily through digital media. How multicultural Islamic education can become a vaccine that can eradicate the virus of radicalism, fundamentalism and exclusivity of Islamic teachings. The results of this research are through the concepts and principles of multicultural Islamic education that will be able to reduce and become a solution to the threat of radicalism, fundamentalism and exclusivity of Islamic teachings that endanger the life of society, nation and religion.